Die dood van dogma? Calvyn se gebruik van die begrippe dogma en doctrina - d’Assonville, V. E. (Koers, 2006)
Dogma’s death? Calvin’s use of the concepts dogma and doctrina In theological as well as in popular articles it has become customary to refer to “dogma” in a negative context. The trend to report negatively on the role and place of dogma in faith, religion and theology is especially obvious in reflections and studies on the sixteenth century Reformers – in particular John Calvin. There is, however, a conspicuous absence of due allowance for important aspects of the understanding and elucidation of historical texts by most authors, including researchers and journalists. The fact that almost 500 years’ history of spiritual trends and philosophical development has already developed between us and the sixteenth century is ignored to a great extent. Concepts are used as if there were no semantic and linguistic development, and this approach leads to superficial evaluation of historical texts and figures. This article points to the gap in existing research and then investigates the interaction between the concepts “dogma” and “doctrina”. It is indicated that a doctrinal treatment of the Word, or even dogmatism, was never an issue in Calvin’s thought. In research on Calvin or in translating his work it is important to be aware of the nuances and wide spectrum of possibilities he worked with when using concepts. These aspects should be considered linguistically and hermeneutically. The danger of reading Calvin eclectically, ignoring the genre and historical background, is also indicated in this article.